CO₂ Emissions and Greenhouse Gas Policy Stringency - An Empirical Assessment - Marcel Probst; Caspar Sauter (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
This paper investigates how greenhouse gas (GHG) policy stringency affects anthropogenic CO2 emissions using a new GHG policy stringency indicator and a structural spatial VAR approach. We estimate an average country-specific elasticity of CO2 emissions to GHG policy stringency, and assess the role of channels over which policy stringency affects CO2 emissions. We then ascertain how GHG policy stringency affects sectoral CO2 efficiency and the sectoral composition of economies. Results indicate that a country with no GHG regulations can achieve a 15% reduction of its CO2 emissions by adopting the stringency level of the most regulated country. In addition, increasing GHG policy stringency improves sectoral CO2 efficiency, and decreases production in CO2 intensive sectors thereby altering the sectoral composition. At last, policy induced CO2 reduction costs in terms of GDP are relatively large, but 4 times lower for developing compared to developed countries.
Keywords: O13; Q53; Q54; Q58; 330; CO2; composition effect; environmental policy stringency; greenhouse gas emissions; impluse reponse functions; spatial VAR; technique effect